1983
DOI: 10.1161/01.cir.67.2.258
|View full text |Cite
|
Sign up to set email alerts
|

Regional blood flow during cardiopulmonary resuscitation in dogs using simultaneous and nonsimultaneous compression and ventilation.

Abstract: SUMMARY We studied regional blood flow (QR) using radiolabeled microspheres and measured hemodynamic variables in 20 anesthetized dogs in normal sinus rhythm and during ventricular fibrillation treated with cardiopulmonary resuscitation (CPR). Nonsimultaneous compression and ventilation CPR (NSCV-CPR) was performed in seven dogs with a pneumatic piston that gave 50 chest compressions/min with an open airway with 10 ventilations at an airway pressure of 33 mm Hg interposed between each fifth and sixth compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Our results are supported by other largeanimal studies, which have demonstrated that simultaneous CCs and ventilation generates higher intrathoracic and vascular pressure and enhances myocardial and cerebral perfusion. 9,10,19,20,[25][26][27] Similar observations in regard to increased blood pressure and carotid blood flow during simultaneous CCs and ventilation have been reported in a human trial. 10 In contrast, interrupting CCs to deliver manual inflations resulted in substantial decreases in the aortic diastolic pressures and coronary perfusion pressures.…”
Section: Discussionsupporting
confidence: 78%
“…Our results are supported by other largeanimal studies, which have demonstrated that simultaneous CCs and ventilation generates higher intrathoracic and vascular pressure and enhances myocardial and cerebral perfusion. 9,10,19,20,[25][26][27] Similar observations in regard to increased blood pressure and carotid blood flow during simultaneous CCs and ventilation have been reported in a human trial. 10 In contrast, interrupting CCs to deliver manual inflations resulted in substantial decreases in the aortic diastolic pressures and coronary perfusion pressures.…”
Section: Discussionsupporting
confidence: 78%
“…Resuscitation time is considered to reflect the severity of ischemic injuries before and during CPR. Some investigators have estimated that, when CPR is begun immediately, cerebral blood flow is 3-15% of normal (Koehler et al 1963;Luce et al 1983;Jackson et al 1984) but decreases progressively as CPR continues (Sharaff et al 1984) and intracranial pressures rise (Guerci et al 1981;Bircher and Safar 1984). Nevertheless, acceptable neurological recovery has been reported even after prolonged CPR (Krug 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been advocated recently, much more strongly than in the past [7,20] because of accumulating evidence that standard CPR may generate inadequate perfusion of the heart in animals [21,22] and that present CPR techniques produce little improvement in resuscitation rates and long-term survival in human beings [23,24].…”
Section: Discussionmentioning
confidence: 99%